Philippine medical thesaurus on anatomy digestive and endocrine systems - Hizon, Christian C.; Faderon, Rosalie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
The study sought to the bridge the communication gap between medical professionals, practitioners, and laymen. It is important because it is necessary for these two groups of people to understand each other through a common linguistic framework. Thus, an effective tool to coordinate this gap was devised and the idea of developing a medical thesaurus prospered. The thesaurus will be helpful in doctor-patient relations since the two groups of individuals have different levels of intellect with regards to medicine. Doctors would use more technical terms while laymen, which include patients, would use simple and common terms. The thesaurus will relate terms of common usage to technical terms.
The top-down approach employed by the researcher served as a basis of the framework of 'domain analysis'. Domain analysis, which is based on deductive method, started from existing implementations, particularly the Medical Subject Headings and ranked translation tools such as dictionaries and supplements suggested by experts from three distinct fields, namely, from the U.P. Sentro ng Wikang Filipino (UP-SWF), Department of Linguistics and the General Reference Section of the U.P. Main Library. Experts' pieces of advice were sought to get their inputs on key issues that ought to be taken into consideration in the design and development of the medical thesaurus, as well as reach consensus on the framework for the study. User surveys, on the other hand, were done through informant work involving medical professionals and practitioners, as well as non-professionals. Analysis and interpretation of terms were done in order to raise issues as well as clarifications that may be beneficial to succeeding batch/es of researchers.
Furthermore, the researcher was able to meet the minimum requirement of 50 translated preferred terms and reached about 55 main entries for both systems out of a 110 MeSH terms analyzed. The author came up with cases as framework of analysis for the data presented and proposed solutions for further study.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Filipino -- Medicine; Subject headings, Filipino -- Anatomy; Subject headings, Filipino -- Digestive systems; Subject headings, Filipino -- Endocrine systems; Filipino Language -- Medical Filipino